Deteksi Dini Penyakit Tumor Sel Darah Myelosit Leukosis melalui Pemeriksaan Ulas Darah - Dewi Ratih Agungpriyono; Hernomoadi Huminto; Sri Estuningsih; Aryani Sismin Satyaningtijas (Institut Pertanian Bogor, 2007)
Myelocytes blood cell tumor in chicken is a disease caused by retrovirus, avian leukosis virus subgroup J (ALV-J). The virus has the same group as human retrovirus (HIV) which caused AIDS, but the avian type possesses oncogenic properties, that could induce cell transformation and tumor formation. ALV-J stimulates the bone marrow's myelocytes and transforms them into tumor cell myelocytoma. The tumor cells then metastasis through the circulatory system causing myeloid leukosis and tumor cells accumulation in various internal organs or myelocytomatosis. This study was done on the base of the leukosis behavior of the tumor. The finding of the metastasis tumor cell in the blood smear examination is thought could be use as the diagnostic clue of the disease. Blood smear from sick chickens are collected and stained with some chemical staining substance such as may grunwald-giemsa, hematoxyllin eosin, periodic acid Schiff, congo red, toluidine blue, and sudan black B. Cytochemistry character of the blood cells was observed using light microscope. The result showed that myelocytes granules were best observed using hematoxyllin eosin, periodic acid Schiff, congo red and toluidine blue while may grunwald-giemsa, and sudan black B could not differentiate the granules. By this method, the field veterinarian will able to screen the suspected chicken flock for myeloid leukosis earlier than the occurrence of tumor formation.